East vs West: Geopolitical Orientations and Language Practices of Residents of Central and Southern Ukraine - Olesya Palinska (Journal of Eurasian Studies, 2023)
The paper based on quantitative and qualitative analysis on data on language attitudes and geopolitical orientations obtained in Central and Southern Ukraine shows significant differences between two regions. The assessment of linguistic changes occurred after the collapse of the USSR in both regions is unequivocal: most participants in open interviews noted a positive trend for the Ukrainian language, including the expansion of functional spheres of its use (on television, in politics, in education) and its higher prestige in society. Post-Soviet changes toward the expansion of the use of the Ukrainian language were viewed positively even by predominantly Russian-speaking respondents, who opposed “Ukrainization” in other aspects. Based on the answers to the questions in the “Geopolitics” and “Identity” blocks of questionnaire, two types of respondents were identified using cluster analysis: (1) “pro-European” and (2) “pro-Russian.” The language preferences of respondents belonging to different clusters differed in the regions studied: while more Ukrainian speakers, both in the Center and in the South, mainly belonged to the first cluster, and more Russian speakers (to a somewhat lesser extent) to the second, speakers who used a mixed idiom known as Surzhik in the Center, were more “pro-Russian,” and in the South, more “pro-European” oriented. That can signal of differences in language attitudes and labeling regarding Surzhik in those regions of Ukraine.